Role of Phospholipase D in Pasteurella haemolytica Leukotoxin-Induced Increase in Phospholipase A(2) Activity in Bovine Neutrophils - Wang, Zuncai (American Society for Microbiology, 1999)
The effects of Pasteurella haemolytica leukotoxin (LKT) on the activity of phospholipase D (PLD) and the regulatory interaction between PLD and phospholipase A(2) (PLA(2)) were investigated in assays using isolated bovine neutrophils labeled with tritiated phospholipid substrates of the two enzymes. Exposure of [(3)H]lysophosphatidylcholine-labeled neutrophils to LKT caused concentration- and time-dependent production of phosphatidic acid (PA), the product of PLD. LKT-induced generation of PA was dependent on extracellular calcium. Both production of PA and metabolism of [(3)H]-arachidonate ([(3)H]AA)-labeled phospholipids by PLA(2) were inhibited when ethanol was used to promote the alternative PLD-mediated transphosphatidylation reaction, resulting in the production of phosphatidylethanol rather than PA. The role of PA in regulation of PLA(2) activity was then confirmed by means of an add-back experiment, whereby addition of PA in the presence of ethanol restored PLA(2)-mediated release of radioactivity from neutrophil membranes. Considering the involvement of chemotactic phospholipase products in the pathogenesis of pneumonic pasteurellosis, development and use of anti-inflammatory agents that inhibit LKT-induced activation of PLD and PLA(2) may improve therapeutic management of the disease.